Analisis Yuridis Peran Digital Forensik Dalam Pembuktian Kasus Penipuan Berkedok Investasi Online (Studi Kasus Doni Salmanan) - Manggala, Bayu Suryadi; Putri, Amelia; Suzeeta, Nala Syandhira; Zalfa, Nabila; Marpaung, Velani Christina; Natalia, Imelda Hera; Nugroho, Andriyanto Adhi (Media Hukum Indonesia (MHI), 2024)
Technology has become an integral element in human life, influencing almost every aspect from daily activities to industrial development. Technology brings various conveniences, such as automation of industrial processes, increased efficiency in various sectors, and fast access to information. Advances in information and communications technology have provided a platform for fraudsters to devise investment schemes that are increasingly sophisticated and difficult to detect. These technology-based investment scams often utilize social media, email and fake websites to attract victims with the promise of high profits in a short time. Technology also allows fraudsters to hide their identities and makes it difficult to trace stolen funds. Education and public awareness are also key in preventing victims from falling into the trap of investment fraud. In order to reduce the risk and impact of technology-based investment fraud, collaboration between government, the technology industry and society is essential.